From centralization to cooperation: The development and reform process of sports venues in China from 1949 to 2022 - Fang, Xuemo; Chen, Yuanxin; Li, Jingyu (Frontiers in Sports and Active Living, 2023)
The management of sports venues has undergone a series of reforms since the People's Republic of China's establishment in 1949. The reform of management right is especially significant. It reflects the government–enterprise relationship and logic of government action. Utilizing the perspective of the government–enterprise relationship, this study systematically reviews the reform model for sports venues to incorporate Chinese characteristics. The aim of this study is to understand the relationship between the People's Republic of China's government and the market through the reforms implemented for the operation and management of sports venues. According to the study, the development and reform of sports venues in China has experienced government centralization, devolution, decentralization, and cooperation. The reform of sports venues' operation and management follows a “market-oriented government-led” model which reflects the government's logic. It is concluded that a “market-oriented government-led” model is essential for the promotion of comprehensive reforms for sports venues with Chinese characteristics.